Vocabulary Analysis On Reading Texts Used By EFL Students - C Sutarsyah (TEFLIN, 2001)
Abstract: The vocabulary in the texts is the aspect that needs to identify. It is claimed that the condition of the words in a text has a great influence to readers comprehension. It is also commonly believed that compreÃÂhension depends on the extent that the words in a text are familiar to the readers. This case study was carried out in the English Education DeÃÂpartment of University of Malang. The aim of the study is to identify and describe the vocabulary in the text and to seek if the text is useful for reading skill development. The reading materials under investigation were a collection of reading passages based on the syllabus (Reading ComÃÂprehension I) and limited to the passages that were used in class during the second semester, 1999. Based on the nature of the investigation, a descriptive qualitative design was applied to obtain the data. For this purpose, some available computer programs were used. They were used to find the description of vocabulary in the texts. The vocabulary analyÃÂses in the texts reveal some constrains. It was found that the texts, conÃÂtaining 7,945 words of 20 different texts, are dominated by low frequency words which account for 16.97% of the words in the texts. In terms of high frequency words occurring in the texts, function words dominate the texts. Of the 50 most frequent words, only two content words (people and say) were found. In the case of word level, it was found that the texts being used have very limited number of words from GSL (General Service List of English Words) (West, 1953). The proportion of the first 1,000 words of GSL only accounts for 44.6%. The data also show that the texts contain too large proportion of words which are not in the three levels (the first 2,000 and UWL). These words account for 26.44% of the runÃÂning words in the texts. Based on the findings, some conclusions were drawn, it is believed that the constraints are due to the selection of the texts which are made of a series of short-unrelated texts (20 different topics). This kind of text is subject to the accumulation of low frequency words especially those of content words and limited of words from GSL.